Development of a Learning Style Diagnostic Assessment Instrument Based on Experiential Learning Theory - Ilman, Eprian Nur; Putri, Aulia; Julita, Niki Harfa; Ristanto, Rizhal Hendi; Isfaeni, Hanum (Gemilang Maju Publikasi Ilmiah (GMPI), 2024)
Assessment is one of the important things to do, especially in differential learning in the independent curriculum currently implemented. Non-cognitive diagnostic assessment is an assessment that is still rarely researched. This research aimed to develop a non-cognitive diagnostic assessment (learning style) at the high school level. The method used in this research is development, or Research and Development (RD). The model used in this research is the ADDIE model. The model consists of five stages, namely the analysis, design, development, implementation, and evaluation stages. This research sample involved all class X students, totaling 30 students. Based on research that has been conducted, shows that non-cognitive diagnostic instruments based on experiential learning theory can be used to determine student learning styles. Based on SHS 22 Tangerang Regency, it is known that students tend to have a learning style. Reflective observational elements have the highest percentage of 76.44% and abstract conceptual elements have the lowest percentage of 71.89%.